Intertextuality and literary reading: a cognitive poetic approach - Panagiotidou, Maria-Eireini. (2012)
The goal of this thesis is to propose a cognitive approach to intertextuality. Intertextuality has attracted the attention of a number of literary scholars interested in discussing the interrelations between literary texts without, however, focusing on how readers create these connections. On the other hand, despite its reader-oriented approach, cognitive poetics has largely neglected the concept.